The Reinstatement and Ontology of Meaning - Bell, Jacob Andrew (Conatus - Journal of Philosophy, 2023)
While science and logic are incredible intellectual endeavors, and while reductionist methodologies have led to advances in knowledge, these methods do not tell the whole story of life, world, and reality. There are real phenomena that, due to their experiential and holistic nature, cannot be properly quantified over by limiting oneself to science, logic, or reductive means of explanation and description. Attempting to understand the world and the human condition requires a plethora of epistemic pursuits to more fully quantify over the plurality of phenomena. Existential meaning is, I argue, an experiential and holistic phenomenon, and as such it cannot be quantified over by reductive endeavors, pure logic, or scientific inquiry. Meaning emerges through the relation of a complex structure (human) in relation to the world, and it exists as an irreducible embodied and embedded experience.